Socio-environmental scenario of an urban microbasin in the eastern Amazon (Research, Society and Development, 2021)
Negative environmental impacts of sensitive ecosystems are constantly found in urban areas, mainly due to anthropic action that significantly alters their natural characteristics. Characteristics of fauna and flora are lost due to disorderly occupation, causing local climate change. The city of Santarém-PA, Brazil, had a significant population increase around the water sources causing a change in the ecosystem of the Urumarí watershed, with greater intensity from 1980 onwards. Of the Urumarí microbasin. In this sense, it was necessary to carry out a study to assess the consequences of disorderly occupation and the lack of basic sanitation services provided to the community around the water body. For this purpose, three (3) sections were delimited and characterized, being the most conserved, the intermediate and the one with consolidated disorderly urbanization, where negative environmental impacts were found in all of them. The characterization was carried out in loco in seasonal periods from 2017 to 2019. The ecosystem's modification is visible and notorious, culminating in the lack of inspection by the competent bodies. The Municipal Master Plan must contain guidelines with guidelines on conservation and stipulate limits for water sources in urban stretches, in addition to being associated with a strong set of regulatory and control measures that facilitate inspection and monitoring by the constituted government, as they are only protected by the Brazilian Forest Code.